Methylation patterns in cell‐free plasma DNA reflect removal of the primary tumor and drug treatment of breast cancer patients - Thomas Liggett; Anatoliy A. Melnikov; Jeffrey R. Marks; Victor Levenson (2010)
Abnormal DNA methylation is a feature of most types of cancer, which is reflected in cell-free circulating DNA in plasma. It is, however, unknown whether surgical removal of the tumor and subsequent therapy induces changes in plasma DNA methylation, which can be used to monitor treatment. In this pilot study, methylation in cell-free plasma DNA of 20 breast cancer patients was determined by the previously developed MethDet-56 technique. Samples at three time points were analyzed-before surgery (baseline), after surgery (to evaluate the effects of resection) and after surgery on tamoxifen therapy (to determine the effects of treatment). Methylation patterns of healthy controls were used as a reference for all comparisons. Seven promoters were differentially methylated (p < 0.05) in at least one comparison; three changed after surgery; another one changed after beginning of tamoxifen treatment; and four were differentially methylated in baseline versus combined treatment samples. Increased methylation of PR PROX, MDGI, PAX 5 and RARβ2 at baseline (presurgery) diminished toward the healthy controls with the lowest methylation in the combined treatment group. Surgery alone decreased methylation in PAX 5 and RARβ2, whereas tamoxifen treatment changed methylation only in the B promoter of ESR1. Methylation patterns in cell-free plasma DNA change after surgery and tamoxifen treatment, most significantly-after combined treatment. The baseline (presurgery) patterns become similar to those of healthy controls, suggesting that methylation patterns in cell-free plasma DNA may be used to monitor treatment.